DEVELOPMENT STRATEGY OF MESIKHAT CLOTH UMKM IN KUTA CANE AREA, SOUTHEAST ACEH - Sari, Indah Purnama; Qarni, Waizul; Rahma, Tri Inda Fadhila (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to identify the strengths and weaknesses in the development of Mesikhat cloth MSMEs in Kuta Cane, Southeast Aceh. Mesikhat is a traditional motif typical of the Alas Tribe with five main colors: red, yellow, white, green, and black, which has high cultural value. The study analyzes the internal and external conditions of MSMEs and development strategies that include creating a conducive business climate, integrated information management, developing an effective marketing system, as well as improving technical capabilities and adapting to modern market needs. In addition, this study highlights the importance of synergy between the government, academics, business actors, and the community in supporting the sustainability and increasing the competitiveness of Mesikhat cloth MSMEs. The results of the study are expected to be strategic recommendations for sustainable business development and oriented towards preserving local culture.Keywords: Meshichat Cloth, MSMEs, Marketing System